The long-term risk of recognized and unrecognized myocardial infarction for depression in older men. Issue 9 (21st March 2016) - Jovanova, O.; Luik, A. I.; Leening, M. J. G.; Noordam, R.; Aarts, N.; Hofman, A.; Franco, O. H.; Dehghan, A.; Tiemeier, H.
Abstract : Background: The association between myocardial infarction (MI) and depression is well described. Yet, the underlying mechanisms are unclear and the contribution of psychological factors is uncertain. We aimed to determine the risk of recognized (RMI) and unrecognized (UMI) myocardial infections on depression, as both have a similar impact on cardiovascular health but differ in psychological epiphenomena. Method: Participants of the Rotterdam Study, 1823 men aged ⩾55 years, were followed for the occurrence of depression. RMI and UMI were ascertained using electrocardiography and medical history at baseline. We determined the strength of the association of RMI and UMI with mortality, and we studied the relationship of RMI and UMI with depressive symptoms and the occurrence of major depression. Results: The risk of mortality was similar in men with RMI [adjusted hazard ratio (aHR) 1.71, 95% confidence interval (CI) 1.45–2.03] and UMI (aHR 1.58, 95% CI 1.27–1.97). Men with RMI had on average [unstandardized regression coefficient ( B ) 1.14, 95% CI 0.07–2.21] higher scores for depressive symptoms. By contrast, we found no clear association between UMI and depressive symptoms ( B 0.55, 95% CI −0.51 to 1.62) in men. Analysis including occurrence of major depression as the outcome were consistent with the pattern of association. Conclusion: The discrepant association of RMI and UMI with mortality compared to depression suggests that the psychological burden of having experienced an MI contributes to the long-term risk of depression.